Membrane fouling of forward osmosis (FO) membrane for municipal wastewater treatment: A comparison between direct FO and OMBR. (1st November 2016) - Sun, Yan; Tian, Jiayu; Zhao, Zhiwei; Shi, Wenxin; Liu, Dongmei; Cui, Fuyi
Abstract: In this work, membrane fouling behavior in a direct forward osmosis (FO) and an osmotic membrane bioreactor (OMBR) for municipal wastewater treatment was systematically investigated and compared. During the long-term operation, much severer flux decline was observed for the direct FO than that for the OMBR. The cake layer was found to be much thicker, together with large amounts of microorganisms growing on the membrane surface in direct FO. Interestingly, no obvious attachment of microorganisms on the membrane surface was observed in the OMBR. The fourier transform infrared spectroscopy (FTIR) and excitation emission matrices (EEM) analyses showed the polysaccharides and proteins were the dominant organic foulants in the fouling layer, and the quantity of the organic substances was also higher in direct FO than that in OMBR. Energy-dispersive X-ray (EDX) results indicated the main inorganic elements in the fouling layer were Ca, Mg, Fe and P, all of which exhibited higher relative percentages in direct FO than that in OMBR. The occurrence of higher contents of microorganisms, organic foulants and inorganic elements in the cake layer caused a higher filtration resistance for the FO membrane in the direct FO. Although more severe membrane fouling was identified in direct FO, the hydraulic and chemical cleaning was more effective on recovering the water permeability of the membrane in direct FO than that in OMBR. Graphical abstract: Highlights: The membrane fouling behaviors were compared between direct FO and OMBR. Much severer flux decline was observed for direct FO than that for OMBR. The foulants on the membrane surface were identified and quantitatively analyzed. Large amounts of bacteria were grown on the membrane in direct FO, but not in OMBR. Hydraulic and chemical cleaning were more effective for the direct FO than OMBR.